The effects of mixing on age of air. Issue 12 (17th June 2014) - Garny, H.; Birner, T.; Bönisch, H.; Bunzel, F.
Abstract Mean age of air (AoA) measures the mean transit time of air parcels along the Brewer‐Dobson circulation (BDC) starting from their entry into the stratosphere. AoA is determined both by transport along the residual circulation and by two‐way mass exchange (mixing). The relative roles of residual circulation transport and two‐way mixing for AoA, and for projected AoA changes are not well understood. Here effects of mixing on AoA are quantified by contrasting AoA with the transit time of hypothetical transport solely by the residual circulation. Based on climate model simulations, we find additional aging by mixing throughout most of the lower stratosphere, except in the extratropical lowermost stratosphere where mixing reduces AoA. We use a simple Lagrangian model to reconstruct the distribution of AoA in the GCM and to illustrate the effects of mixing at different locations in the stratosphere. Predicted future reduction in AoA associated with an intensified BDC is equally due to faster transport along the residual circulation as well as reduced aging by mixing. A tropical leaky pipe model is used to derive a mixing efficiency, measured by the ratio of the two‐way mixing mass flux and the net (residual) mass flux across the subtropical boundary. The mixing efficiency remains close to constant in a future climate, suggesting that the strength of two‐way mixing is tightly coupled to the strength of the residual circulation in the lower stratosphere. This implies that mixing generally amplifies changes in AoA due to uniform changes in the residual circulation.